Challenge Match The Stakes Grow Higher for Global Leaders - Cranford, Shannon (Center for Creative Leadership, 2007)
Leading globally is extremely complex. The differences between the requirements of leadership at a local level and of leadership at the global level are exponential. To learn about the specific challenges faced by global leaders, CCL conducted interviews with senior global leaders. Analysis of the responses revealed six common themes.
Title from content provider